1997
DOI: 10.1046/j.1365-3083.1997.d01-439.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirally Induced Mouse Anti‐TCR Monoclonals can Synergize the In Vitro Proliferative T Cell Response to Bacterial Superantigens

Abstract: Dehghanpisheh K, Marchalonis JJ. Retrovirally Induced Mouse Anti-TCR Monoclonals can Synergize the In Vitro Proliferative T Cell Response to Bacterial Superantigens. Scand J Immunol 1997;45:645-654 Antibodies directed against the b chain of the T-cell receptor (TCR) have been detected in animals and in humans in a number of distinct immune states that do not involve direct immunization with either T cells or TCR epitopes. When C57Bl/6 mice are infected experimentally with the LP-BM5 retrovirus mixture they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…The fact that the titers of these anti-TCR Ab's increase not only in autoimmune diseases (experimental and human) (15,(17)(18)(19), but also during the course of viral infections (53)(54)(55) or alloimmunization (58), supports the concept that the increase in anti-TCR Ab titer may play a role not only in the regulation of autoimmune responses (and diseases), but also more generally in the regulation of any immune response. We are currently investigating this possibility in an immune response model to elucidate the possible function of anti-TCR Ab's in immunoregulation and their relationship to T reg cells.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The fact that the titers of these anti-TCR Ab's increase not only in autoimmune diseases (experimental and human) (15,(17)(18)(19), but also during the course of viral infections (53)(54)(55) or alloimmunization (58), supports the concept that the increase in anti-TCR Ab titer may play a role not only in the regulation of autoimmune responses (and diseases), but also more generally in the regulation of any immune response. We are currently investigating this possibility in an immune response model to elucidate the possible function of anti-TCR Ab's in immunoregulation and their relationship to T reg cells.…”
mentioning
confidence: 75%
“…In contrast, we detected a spontaneous increase in the levels of such Ab's in MG patients in the absence of immunization, consistent with the notion that these Ab's are induced naturally during the course of the disease. Other studies have reported the presence of Ab's against the CDR1 but not the CDR2 peptide in systemic lupus erythematosus and rheumatoid arthritis patients (15), and during the course of viral infection in mice and humans (53)(54)(55). These differences may be due to the arbitrary scanning of the whole TCR chain and the use of synthetic 16-mer peptides overlapping by five residues, an approach that may miss potential immunogenic regions (15,56).…”
mentioning
confidence: 99%
“…39 In our own studies with murine mAAbs to TCR Vb epitopes, we documented that such antibodies acted synergistically with superantigens in the activation of T-cell subsets. 24 Furthermore, studies using therapeutic preparations of purified human IgG document the immunoregulatory role of NAAbs in a variety of human diseases, with an anti-TCR specificity beneficial in Kawasaki's disease. 12 We have determined the affinity of one mAAb, OR2, for binding to the single-chain TCR and the CDR1 peptide on which all of the anti-TCR mAAbs were selected.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,17,18 It has been proposed that NAAbs against the TCR may serve in immunoregulation of T cells. 24 This theory seems plausible given the nature of the specificity of these molecules and the understanding that antibodies play a critical role in neutralizing antigens through the interaction of the antibody-combining site with specific antigen. To test this premise, monoclonal NAAbs against the TCR are required to carry out the appropriate assays for determining their functional capacities.…”
Section: Introductionmentioning
confidence: 99%
“…The role of natural autoantibodies to TCR Vb domains in immunomodulation is supported by observations that purified polyclonal human IgG (intravenous immunoglobulin; IVIG) has a therapeutic effect on Kawaski's disease (Kazatchkine and Kaveri, 2001), an inflammatory disease showing restricted Vb expression, and that IVIG modulates the expression of particular individual Vb gene segments in T cells induced by Staphyloccal enterotoxin B superantigen in vitro (Baudet et al, 1996). We were able to generate murine (Dehghanpisheh and Marchalonis, 1997) and human monoclonal antibodies against these markers. The murine monoclonals were synergistic with bacterial superantigens selective to different Vb subsets (Dehghanpisheh and Marchalonis, 1997).…”
Section: Naturally Recognized Peptide Autoepitopes Of Tcr Variable Domentioning
confidence: 99%